Greenland Ice Sheet Contribution to 21st Century Sea Level Rise as Simulated by the Coupled CESM2.1-CISM2.1 - Muntjewerf, L. (author); Petrini, M. (author); Vizcaino, M. (author); Ernani da Silva, C. (author); Sellevold, R. (author); Scherrenberg, Meike D.W. (author); Thayer-Calder, Katherine (author); Bradley, Sarah L. (author); Lenaerts, Jan T.M. (author) (Geophysical Research Letters, 2020)
The Greenland Ice Sheet (GrIS) mass balance is examined with an Earth system/ice sheet model that interactively couples the GrIS to the broader Earth system. The simulation runs from 1850 to 2100, with historical and SSP5-8.5 forcing. By the mid-21st century, the cumulative GrIS contribution to global mean sea level rise (SLR) is 23 mm. During the second half of the 21st century, the surface mass balance becomes negative in all drainage basins, with an additional SLR contribution of 86 mm. The annual mean GrIS mass loss in the last two decades is 2.7-mm sea level equivalent (SLE) year −1 . The increased SLR contribution from the surface mass balance (3.1 mm SLE year −1 ) is partly offset by reduced ice discharge from thinning and retreat of outlet glaciers. The southern GrIS drainage basins contribute 73% of the mass loss in mid-century but 55% by 2100, as surface runoff increases in the northern basins. Physical and Space Geodesy